SYSTEMATIC LITERATURE REVIEW: THE RELATIONSHIP BETWEEN CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) AS A PREVENTION OF DIARRHEAL DISEASE - Nurul Maghfirah Junaid; Armanto Makmun; Abbas Zavey Nurdin; Husni Esa Darussalam; Ardiyanto (International Medical Journal Corp. Ltd, 2026)
Diarrhea remains a global public health problem, especially in developing countries, one of which is Indonesia, with a high incidence rate in vulnerable groups such as toddlers. The implementation of Clean and Healthy Living Behavior (PHBS) is an essential preventive strategy in reducing the incidence of diarrhea, but previous research results have shown varying findings. This study systematically examines the relationship between the implementation of Clean and Healthy Living Behavior (PHBS) and the prevention of diarrheal disease based on current scientific evidence. This study uses a systematic literature review design with the PICOS approach. Literature searches were conducted through Google Scholar, PubMed, ScienceDirect, ResearchGate, and ProQuest for articles published between 2021 and 2025 in Indonesian and English. Study selection was carried out through title and abstract screening stages, followed by full-text review according to criteria. A total of 20 articles were analyzed descriptively and systematically. Most of the literature reveals a significant relationship between the implementation of PHBS and a reduced risk of diarrhea incidence. Individuals or groups with good PHBS implementation have a lower risk of diarrhea compared to those who do not implement PHBS optimally. The PHBS components that play a dominant role include hand hygiene practices with soap, use of clean water sources, use of proper sanitation facilities, and hygienic food and waste management. Factors influencing the effectiveness of PHBS include knowledge, attitudes, socioeconomic conditions, availability of sanitation facilities, as well as environmental support and health policies. The implementation of PHBS is an effective, evidence-based preventive strategy for preventing diarrheal disease. Strengthening education and improving access to adequate sanitation are needed to support sustainable public health interventions.